User- Centered Methodologies for Requirements Engineering: A Comparative Analysis using ISO/IEC/IEEE 29148 - Alex Llanque; Vaneza Flores; Abraham Dávila Ramón (ReCIBE, 2022)
(BACKGROUND) Requirement engineering is a fundamental process of the software development life cycle processes that allows defining the functionalities, quality and scope of a software. Requirement engineering is a human-intensive participation process and that have in ISO/IEC/IEEE 29148 a standard that defines a set of process (activities, tasks, information items, etc.) that provide support for its formalization. However, in the software industry there are many types of deficiencies have been reported. In this context, proposals for User-Centered Methodologies for Requirement Engineering have emerged and need to be studied to determine their alignment to the ISO 29148. (OBJETIVES) The objective of this study is to compare User-Centered Methodologies for Requirement Engineering taking process elements from ISO 29148 as criteria. (METHODS) For this research, a systematic mapping study and a comparative analysis of the UCMREs obtained were performed. (RESULTS) In the systematic mapping study, 4,463 studies were obtained from three relevant digital databases in the first stage, and after the selection process, five User-Centered Methodologies for Requirement Engineering were identified. These methodologies were characterized and analyzed from process elements perspective for comparison to ISO 29148. (CONCLUSIONS) The DoRCU methodology is the closest to ISO 29148, followed by Ammeth and Borja methodologies; and the XRE methodology is the most away to ISO 29148.